Professional performance in assisting male victims of violence: invisible complexity and ambiguities (Research, Society and Development, 2021)
The current Brazilian scenario of research that prioritizes violence against boys is scarce, especially those that study polyvictimizations, in other words, the occurrence of more than one type of violence for the same victim. The polyvictimization scenario is complex and brings as a consequence for the polyvictim an accumulation of symptoms, reason why it is essential that their rights are guaranteed through intersectoral and interdisciplinary care that accounts for the extent of the phenomenon. This text is part of a broad action-research, with qualitative bias and still in progress, and aims to present the perceptions of professionals who belong and work in the public service in one of the states of Brazil about the (poly) victimization of boys and their own professional practices. Twenty-one professionals from seven different sectors that guarantee the rights of children were interviewed. The sectors are: social assistance, education, justice, public ministry, health, public security and civil society. After reflexive thematic analysis, two themes are discussed, structured from the reflections and opinions from the participants: “Polyvictimization: deep roots, but not visible” and “Professional performance with the (poly) victimization of boys”. In future research, it is suggested to conduct similar research in other states of Brazil, so that knowledge about polyvictimization is expanded and it is possible to enable professionals working with the theme.